Preparo e caracterização de compósitos de carvão ativado e óxido de ferro - Vissotto, Juliano Parizotto (2017)
The present study had as objective the preparation and characterization of activated carbons composites and iron oxides. The activated carbons were impregnated in two different proportion. In a beaker, 27 g of FeSO4. 7H2O were dissolved in distilled water, and then were added the activated carbons (weight of 30 g or 60 g) which were kept under mechanical agitation for 2 hours. After heating at 80 ºC, an alcaline solution (14 g of KOH and 2,1 g of KNO3 dissolved in 260 ml of distilled water) was added, slowly and with constant agitation, to promote the precipitation of iron oxides. The suspension os activated carbon and iron oxide remained at 80 ºC for 1 hour, and then kept at rest fr approximately 24 hours. The composites were washed with destilled water to remove the fine particles and dried in an oven at 105 ºC for 8 hours. The composites prepared showed 4,53% and 5,26% of iron oxide. The materials obtained were characterized by means of thermogravimetric analysis and x-ray diffraction in which it was identified the presenceof goethite and magnetite. A decomposition of H2O2 was conducted, in which the samples containing ferrous oxide were more effective than the sample activated carbon without iron oxide. Thus, the composites of activated carbon and iron oxide combine the chacteristics of adsorption and oxidation, making it promising for use in industrial processe.